Associations between HIV Testing and Consent Policies among Sexually Active Adolescents: Differences by Sexual Behavior. Issue 7 (3rd July 2022) - Phillips, Gregory; Wang, Xinzi; Ruprecht, Megan M.; Stephens, Reno; Costa, Diogo; Beach, Lauren B.; Janulis, Patrick
ABSTRACT: HIV incidence remains high among US youth, especially among sexual minority youth. However, only half of youth with HIV are aware of their status. One potential explanation for low HIV testing rates is that restrictive policies may prevent minors from access HIV testing due to parental consent requirements. Using pooled data from the local Youth Risk Behavior Survey, we assessed whether state HIV testing laws, including age restrictions and explicit inclusion of HIV in STI testing consent laws, were associated with differences in HIV testing rates; differences by sexual behavior were also examined. Among female youth, policies were not associated with HIV testing. However, among male youth, both the presence of age restrictions and explicit inclusion in STI services were significantly associated with increased odds of HIV testing. Results indicate that policy changes may be effective at increasing testing among male youth who have sex with other males.